Pengembangan Media Pembelajaran Interaktif ECORAN (Ekosistem Rantai Makanan) Pada Materi Ekosistem di Kelas V SD - Fani Sri Aprilia; Mohammad Fahmi Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to develop an interactive learning media product called ECORAN (Ecosystem Food Chain) based on Genially, intended for fifth-grade elementary students learning about ecosystems. This research was conducted at SDN Mekarwangi selected through simple random sampling. The study applied the Research and Development (R&D) method and involved three testing stages: a small group (5 students), a large group (10 students), and implementation testing (26 students). Data were collected using interviews, observations, validation instruments, and pretest-posttest evaluations. The results showed that the ECORAN media is feasible and effective. Media expert validation scored 94%, material expert validation scored 96%, and language expert validation scored 100%. Student learning outcomes showed significant improvement after using the media. The ECORAN media proved to be an effective tool to support engaging and meaningful science learning.